Perspectives of higher education teachers about distance education - Torres, Maricel Karina López; Oliveira, Paulo Cristiano de; Nunes, Carolina Schmitt; Nakayama, Marina Keiko (Universidade Estadual de Campinas, 2014)
Distance education (DE) has resulted in significant changes in the Brazilian educational context, especially in higher education, which has been considerably enhanced the openings. The objective of this research is to present the perception of higher education teachers who work in public and private institutions, about the institutionalization and practice of distance education. This is a research interpretive, exploratory. Data collection involved document analysis and in-depth interviews with six teachers in higher education have been intentionally selected, in the states of Santa Catarina and São Paulo. The results of the narrative analysis showed that the perspective of DE, from the perspective of teachers, is focused on a critical analysis of the educational reality, being that they have followed the movement of the institutions with interest in distance education and demonstrate concerned with the direction the expansion of the modality, especially with regard to precarious of the teaching role at the expense of overvaluation of technology and reduce educational costs. Concerning the vision of the future of DE there are differences in Brazil - apparently, some tend to be optimistic while others tend to be pessimistic. Is understood that the expansion of the distance learning in higher education is an important process for the Brazilian educational reality, as controversial, hence the relevance of this study.